PENGUATAN LIFE SKILLS PESERTA DIDIK DENGAN PENDEKATAN EKONOMI KREATIF - Malaikosa, Yes Matheos Lasarus (Idaarah: Jurnal Manajemen Pendidikan, 2021)
Abstract: Strengthening Life Skills Learners with a Creative Economic Approach: Case Studies in Vocational The impact of the ASEAN economic community on the development of industry 4.0 is increasingly massive, the education system requires a new breakthrough to respond to the development of industry 4.0. The Indonesian government continues to make changes and developments in the field of education to prepare students to become human beings who are knowledge able, capable, creative, independent, and responsible. Vocational education aims to prepare graduates to be ready to work and innovate. The main purpose of this study is to determine the content of the creative economy in shaping the life skills of students. This research uses a qualitative case study design approach, to understand the meaning of events and interactions involving school principals, teachers, students, school staff, as well as the business world and industry, so that researchers can understand concepts and strategies related to SMK management. Based on the results of the study, it was concluded that the content of the creative economy is one of the creative approaches that need to be integrated into the curriculum and learning to build honest, responsible, confident, tenacious, disciplined, and highly competitive attitudes for students, teachers always use various methods and approaches are compiled in the curriculum and can be integrated in the learning process. The formation of life skills as a provision of skills to face and solve the difficulties of life and life, actively and creatively seek and find solutions to overcome problems. Abstrak: Penguatan Life Skills Peserta Didik dengan Pendekatan Ekonomi Kreatif: Studi Kasus di SMK Dampak masyarakat ekonomi ASEAN terhadap perkembangan industri 4.0 semakin masif, sistem pendidikan membutuhkan gebrakan baru untuk merespon perkembangan industri 4.0. Pemerintah indonesia terus melakukan perubahan dan pengembangan di bidang pendidikan untuk mempersiapkan peserta didik agar menjadi manusia yang berilmu, cakap, kreatif, mandiri, dan bertanggung jawab. Pendidikan kejuruan bertujuan untuk mempersiapkan lulusan untuk siap bekerja dan berinovasi. Tujuan utama dari penelitian ini adalah untuk mengetahui muatan ekonomi kreatif dalam membentuk life skills peserta didik. Penelitian ini menggunakan pendekatan kualitatif rancangan studi kasus, untuk memahami makna peristiwa serta interaksi dengan melibatkan kepala sekolah, guru, peserta didik, staf sekolah, serta dunia usaha dan dunia industri, sehingga peneliti dapat memahami konsep serta strategi berkaitan pengelolaan SMK. Berdasarkan hasil penelitian diperoleh kesimpulan bahwa muatan ekonomi kreatif merupakan salah satu pendekatan kreatif yang perlu diintegrasikan ke dalam kurikulum dan pembelajaran untuk membangun sikap jujur, bertanggung jawab, percaya diri, ulet, disiplin, dan memiliki daya saing yang tinggi bagi peserta didik. Guru selalu menggunakan berbagai metode dan pendekatan yang disusun dalam kurikulum dan dapat diintegrasikan dalam proses pembelajaran. Pembentukan keterampilan life skills sebagai bekal keterampilan untuk menghadapi dan memecahkan kesulitan hidup dan kehidupan, secara aktif dan kreatif mencari serta menemukan solusi untuk mengatasi permasalahan.